Autism spectrum disorders and intestinal microbiota - De Angelis, Maria; Francavilla, Ruggiero; Piccolo, Maria; De Giacomo, Andrea; Gobbetti, Marco (Gut microbes, 2015)
Through extensive microbial-mammalian co-metabolism, the intestinal microbiota have evolved to exert a marked influence on health and disease via gut-brain-microbiota interactions. In this addendum, we summarize the findings of our recent study on the fecal microbiota and metabolomes of children with pervasive developmental disorder-not otherwise specified (PDD-NOS) or autism (AD) compared with healthy children (HC). Children with PDD-NOS or AD have altered fecal microbiota and metabolomes (including neurotransmitter molecules). We hypothesize that the degree of microbial alteration correlates with the severity of the disease since fecal microbiota and metabolomes alterations were higher in children with PDD-NOS and, especially, AD compared to HC. Our study indicates that the levels of free amino acids (FAA) and volatile organic compounds (VOC) differ in AD subjects compared to children with PDD-NOS, who are more similar to HC. Finally, we propose a new perspective on the implications for the interaction between intestinal microbiota and AD.